PERLINDUNGAN HUKUM BAGI PEMEGANG HAK CIPTA TERHADAP PEMBAJAKAN FILM PADA APLIKASI TELEGRAM - NIM. A1011191043, JAMILAH (Fakultas Hukum Universitas Tanjungpura, 2024)
ABSTRACT A phenomenon of film piracy through the Telegram application can cause material losses. Perpetrators of piracy can be charged under Article 9 in conjunction with Article 113 of Law Number 28 on copyright and Article 32 in conjunction with Article 48 of Law Number 19 of 2016 on information and Electronic Transactions. Therefore, the author is interested in conducting research and discussing it under the title: